Terroryzm sponsorowany przez państwa. Casus bliskowschodnich państw-sponsorów - Wejkszner, Artur (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The point of interest in this paper is the issue of state-sponsored terrorism. The essence of this form of terrorism is the intentional (indirect or direct) support, offered by state sponsors to terrorist organizations, and the intention to let them achieve their political, strategic or tactical goals, usually concerning the citizens, governments or the territory of third-party countries. The paper presents a classification of the range of such support and concentrates on the analysis of the motives and means applied by the state sponsors. Owing to historical conditions and the range and scope of support granted, the paper uses the examples of Iran, Syria and Iraq. Only the former two states offer permanent support to terrorist organizations in the Middle East. After the collapse of Saddam Hussein’s regime, Iraqi authorities have abandoned this activity as it was actually harmful to the interests of their country.